Emotion-Focused Coping dalam Perspektif Psikologi Barat dan Islam sebagai Strategi Dakwah: Analisis Komparatif Konseptual dan Praktik Keteladanan Nabi - Sofyan Atstsauri; Sukataman Sukataman; Idlofi Idlofi; Fina Lailatul Masruroh; Ahmad Murtaza (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2025)
This study examines the concept of emotion-focused coping in Western psychology and engages it in dialogue with the model of emotional regulation in Islamic psychology. In Western psychological tradition, emotion-focused coping is understood as an individual’s strategy to manage emotional responses to stressful situations that are difficult or impossible to change. This study employs a qualitative approach using library research and comparative analysis of Western psychological literature and primary sources of Islamic psychology, including the sirah of Prophet Muhammad (peace be upon him) and thematic tafsir studies. The findings indicate that the concept of emotional regulation equivalent to emotion-focused coping has long existed in Islamic scholarly heritage and was practiced concretely by the Prophet Muhammad (peace be upon him), particularly during the Battle of Uhud. In the face of defeat, which had the potential to trigger anger and emotional dysfunction, the Prophet demonstrated emotional regulation through patience, withholding anger, forgiving the mistakes of his companions, building social support through consultation, and relying on Allah Almighty through tawakkul. These practices of emotional regulation not only served to stabilize the personal and collective psychological state of the Muslim community, but also became part of the Prophet’s da’wah strategy, emphasizing emotional education, character formation, and spiritual empowerment as foundational elements for sustaining the mission of Islamic da’wah amid highly stressful circumstances. The findings reaffirm that Islamic psychology offers a holistic and transcendental model of emotion-focused coping, integrating emotional, social, and spiritual dimensions, while simultaneously enhancing the effectiveness of da’wah through the exemplary conduct of the Prophet. This model enriches modern psychological discourse by providing ethical and religious perspectives in emotional management.